Renal effects of HMG-CoA reductase inhibition in a rat model of chronic inhibition of nitric oxide synthesis - Lecian, Dalibor; Demová, Hana; Lodererová, Alena; Ždychová, Jana; Klučková, Hana; Teplan, Vladimír; Voska, Luděk; Komers, Radko (Kidney & blood pressure research, 2006)
BACKGROUND/AIMS: In addition to their lipid-lowering effects, HMG-CoA reductase inhibitors (statins) induce a variety of pleiotropic actions that have been recently studied in the area of cardiovascular and renal protection. In the present studies we sought to determine whether statins retain beneficial effects in the experimental model of NO deficiency achieved by chronic administration of a pressor dose of L-arginine analogue N-nitro-L-arginine-methyl ester (L-NAME). METHODS: To address this issue, blood pressure (BP), renal function (GFR), and albuminuria were determined in rats treated for 4 weeks with L-NAME, L-NAME + atorvastatin (ATO), and in untreated controls. In addition, renal cortical protein expression of caveolin 1 (CAV1), vascular endothelial growth factor (VEGF), and activity of RhoA were also determined. RESULTS: L-NAME administration resulted in sustained elevation of BP, decreased GFR, and in higher albuminuria as compared to control animals. Co-administration of ATO with L-NAME normalized albuminuria and prevented decreases in GFR in L-NAME rats without having an impact on pressor effects of L-NAME. CAV1 protein expression was similar in all groups of rats. In contrast, VEGF expression and RhoA activity was increased in L-NAME-treated animals, and normalized with co-administration of ATO. CONCLUSION: Treatment with ATO exerts early nephroprotective effects in the NO-deficient model of hypertension. These effects could be mediated by amelioration of VEGF expression and reduction of RhoA activity. Copyright 2006 S. Karger AG, Basel.
Keywords: nemoci ledvin; financování organizované; Analysis of Variance; Animals; hypertenze; Kidney Glomerulus; Rats, Wistar; albuminurie; Glomerular Filtration Rate; vaskulární endoteliální růstový faktor A; glomerulus; Caveolin 1; Heptanoic Acids; Vascular Endothelial Growth Factor A; Kidney Diseases; krevní tlak; statiny; Models, Animal; Financing, Organized; analýza rozptylu; Hypertension; Male; Hydroxymethylglutaryl-CoA Reductase Inhibitors; NG-nitroargininmethylester; Albuminuria; NG-Nitroarginine Methyl Ester; Pyrroles; Nitric Oxide; kyseliny heptylové; kaveolin 1; krysa rodu Rattus; rhoA protein vázající GTP; oxid dusnatý; zvířata; mužské pohlaví; Blood Pressure; pyrroly; rhoA GTP-Binding Protein; Rats; hodnoty glomerulární filtrace; modely u zvířat; potkani Wistar